Inscritos e colagens nas celas das transexuais no complexo penitenciário Manoel Carvalho Neto (COPEMCAN): um estudo do ethos argumentativo - Reis, Geovaneide Santos dos (2022)
This master's dissertation, whose title is Enrolled and collages in the cells of transsexuals in the Manoel Carvalho Neto Penitentiary Complex (Copemcan): a study of the argumentative ethos, has the general objective of analyzing the construction of the ethos in inscribed and religious collages present in cells of transsexuals in a prison in Sergipe, in order to reveal values, beliefs and expectations present in the speeches of incarcerated transsexuals, in addition to reflecting on the stigmas that feed gender prejudice, reinforce the exclusion of minority groups and encourage criminality. The study, with regard to the process of collecting information and defining concepts for the construction and validation of analyses, uses bibliographic research, based on references in books, newspapers, articles, dissertations and theses on the argumentative ethos and the struggle LGBTQIA+, which was carried out between 2020 and 2021. Still methodologically, it is a qualitative research. More than 20 images were collected by the researcher and suitably trained and educated staff at the Complexo Penitenciário for the composition of the corpus, obtained through photographs taken from a cell phone camera, in addition to responses from a press conference with the inmates. The analysis was based on theorists of Discursive Argumentation and Rhetoric, such as Aristotle (2005, 2007), Amossy (2005), Maingueneau (2006), Reboul (2000); in addition to Goffman (2017), for the concept of stigma, Gitahy (1999), with the study of subscribers, and Cohen (1989) on collages. It was observed, through the analysis, the construction of a religious ethos that can reveal the search of the speakers to persuade the audience, modifying possible previous negative ethos related to their criminal history and even to their condition of transsexuals, still, many times , judged as sinful and wrong by the church and society in general, when revealing their beliefs, regrets and search for salvation, according to the religious discourses to which they have access and which they reproduce in their speeches. Allied to this religious ethos, it reveals a critical ethos that denounces the conditions of incarcerated transsexuals and asks for respect and equality.